Pengaruh Kualitas Produk Terhadap Citra Merk Dan Dampaknya Terhadap Keputusan Pembelian Konsumen (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
This study aims to analyze empirical evidence of the influence of product quality and brand image of Alfamart-labeled products on consumer purchasing decisions on Alfamart Kramat Pulo 2. Smple obtained by 100 respondents. The sampling technique uses non probability sampling, which is a sampling technique that provides equal opportunities for each element (member) of the population to be selected as sample members. The results showed that product quality had a positive and significant effect on brand image, so that if product quality was getting better the brand image would increase. Empirically the brand image has a positive and significant influence on purchasing decisions so that if the brand image of the product is increasingly attached to the minds of consumers, purchasing decisions will increase. Furthermore, empirical testing, product quality has a positive and significant effect on purchasing decisions. In the fourth hypothesis, product quality has a positive and significant effect on consumer purchasing decisions through brand image.